Pengaruh Struktur Modal, Pertumbuhan Perusahaan, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan yang Terdaftar di ISSI Tahun 2019-2023 - Muslimatunnisa Safitri; Usdeldi Usdeldi; Nurrahma Sari Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine the effect of capital structure, company growth and profitability on company value in companies registered with ISSI Tshun 2019-2023. The method used in this research is a quantitative method. This research uses secondary data in the form of company annual reports which are the research sample and can be obtained from the Indonesian Stock Exchange website. The sample was taken using a purposive sampling technique so that the total was 11 companies. The data obtained and collected is then processed using the application. The data analysis techniques used are descriptive statistics, classical assumption testing, panel data regression analysis, and hypothesis testing. Based on the research results, it shows that partially, capital structure has a significant influence on company value, while company growth and profitability have no influence on company value. Simultaneously, capital structure, company growth and profitability have no effect on company value.